Qualitative Analysis of COVID-19 Vaccine Reactogenicity in Banjarmasin City, South Kalimantan During the Pandemic - Muliyani Muliyani; Nazhipah Isnani; Rahmi Annisa; Juwita Ramadhani (CV. Inara, 2025)
The World Health Organization (WHO) officially recognized COVID-19 as a pandemic. By March 29, 2020, global cases had reached 634,835 with 33,106 fatalities. In Indonesia, there were 1,528 confirmed infections and 136 deaths. According to Indonesia's Presidential Regulation No. 99 of 2020, the government is expediting the acquisition of COVID-19 vaccines and the vaccination program to combat the pandemic. COVID-19 has spread extensively across nearly all provinces in Indonesia. The government remains committed to gradually delivering safe, high-quality, and effective vaccines. Despite these efforts, many people remain hesitant about vaccination due to concerns over side effects and vaccine safety. This study aims to qualitatively analyze the reactogenicity of COVID-19 vaccines. Using a descriptive observational qualitative design, informants were selected through purposive sampling. Reported side effects include drowsiness, injection site pain, increased appetite, fever around 38-39°C, weakness, recurrence of asthma, chest tightness, cough, and runny nose. The most common reactions observed were fever up to 39°C (18.51%) and vomiting (11.11%).